Pengaruh Metode Drill & practice Terhadap Kemampuan Membaca Al-Qur’an Santriwati di Pondok Pesantren Darut Tafsir - Eifa Siti Luciana Al-Hakim; Syarifah Gustiawati Mukri; Qurroh Ayuniyyah (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study was motivated by the fact that some seventh-grade female students still experienced difficulties in reading the Qur’an, particularly in the aspects of correct pronunciation (makharij al-huruf), application of tajwid rules, fluency, and reading accuracy. In the learning process at Darut Tafsir Islamic Boarding School, the Drill & practice method had been implemented in Qur’an reading instruction; however, its implementation had not been carried out consistently. This study aimed to describe the implementation of the Drill & practicemethod, identify the Qur’an reading ability of the students, and analyze the influence of the Drill & practicemethod on the Qur’an reading ability of seventh-grade female students at Darut Tafsir Islamic Boarding School. This research employed a quantitative approach with an explanatory research design. Data were collected through observation, questionnaires, Qur’an reading tests, and documentation. The data were analyzed using descriptive statistics and simple linear regression analysis. The results showed that the implementation of the Drill & practice method was categorized as fairly good, with a mean score of 65.31. Meanwhile, the students’ Qur’an reading ability was categorized as high, with a mean score of 89.02. The difference between these categories indicates that Qur’an reading ability is influenced not only by the implementation of the Drill & practicemethod but also by other factors, such as habituation to Qur’an reading within the boarding school environment, learning motivation, and guidance provided by teachers. The regression analysis revealed a positive and significant influence of the Drill & practicemethod on the students’ Qur’an reading ability, as indicated by a significance value of 0.000 < 0.05. The correlation coefficient (R) of 0.907 indicated a very strong relationship, while the coefficient of determination (R²) of 0.822 showed that the Drill & practice method contributed 82.2% to the students’ Qur’an reading ability, whereas the remaining 17.8% was influenced by other factors beyond the scope of this study.